A design of wideband high-power 3-dB quadrature coupler using defected ground structure for status data transmitting system - The Anh Nguyen Dinh; Long Hoang Duc; Duong Bach Gia; Dragos Dancila (Institute of Advanced Engineering and Science, 2020)
The paper presents a wideband 3-dB quadrature coupler designed for operation at 2 GHz. The presented coupler is based on a broadside-coupled suspended structure in combination with a proposed defected ground structure (DGS) allowing for high power, wide-band and improved harmonic suppression performance. The experimental results show 0.2 dB of insertion loss, return loss of better than 18 dB and isolation of better than 25 dB in the frequency range from 1.74 to 2.67 GHz. The proposed coupler is able to be integrated in the status data transmitting system, which is suitable for vessel monitoring. The fundamental characteristics of the implemented coupler have been measured and verified.